ОСОБЛИВОСТІ РОБОТИ АВТОНОМНИХ ЗАРЯДНИХ СТАНЦІЙ ЕЛЕКТРОМОБІЛІВ З ВИКОРИСТАННЯМ ФОТОЕЛЕКТРИЧНИХ УСТАНОВОК ТА БУФЕРНИХ АКУМУЛЯТОРІВ ЕНЕРГІЇ - Павлов, В.Б.; Будько, В.І.; Кириленко, В.М.; Будько, М.О.; Кириленко, К.В. (Інститут електродинаміки Національної академії наук України, 2019)
The mathematical description of the system of an autonomous charging station of electric vehicles using photovoltaic systems is proposed. The necessary energy intensity of the buffer energy accumulator is substantiated in the case of the implementation of autonomous charging stations of electric vehicles with the use of photovoltaic installations as generators of electric energy. The features of electric power supply of the charging station on the basis of real data of intensity of solar radiation are considered. A range of capacities of a photoelectric installation has been established at which the charge of a buffer accumulator is ensured, taking into account actual solar indicators. References 12, figures 7.